2022
DOI: 10.1097/yco.0000000000000800
|View full text |Cite
|
Sign up to set email alerts
|

The current evidence for substance use disorder apps

Abstract: Purpose of reviewNew mHealth (smartphone) apps for substance use disorders (SUD) are emerging at an accelerated rate, with consumer choice typically guided by app-store user ratings rather than their effectiveness. The expansive reach, low-cost and accessibility of mHealth apps have driven their popularity and appeal as alternatives to traditional treatment; as such, rigorously establishing their effectiveness is of paramount importance. Recent findingsSeveral systematic reviews conclude that the evidence-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…They also concluded that RSS had the greatest efficacy. Manning et al 22 identified RSS as having the best evidence; however, they added that CBT and approach-based modification (ABM) modules showed promise. Staiger et al 23 identified 12 studies examining alcohol and illicit SUD application-based interventions.…”
Section: Resultsmentioning
confidence: 99%
“…They also concluded that RSS had the greatest efficacy. Manning et al 22 identified RSS as having the best evidence; however, they added that CBT and approach-based modification (ABM) modules showed promise. Staiger et al 23 identified 12 studies examining alcohol and illicit SUD application-based interventions.…”
Section: Resultsmentioning
confidence: 99%